Relationship between Parental Attention and Student Learning Motivation in Science Subjects - Anita Amelia Ole; Blessifaith Pearly Christianti Mamangkey (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is a quantitative research that is descriptive and correlation in nature. Attitude of parental attention is a form of support given to increase student motivation when learning to. This research is to find the relationship between parental attention and students' learning motivation in science subjects. Researchers conducted this study because based on interviews conducted with several students in one of the public schools in North Sulawesi, it was found that there were some students who felt they did not get enough attention from their parents, because their parents were busy with work to meet family needs so that caused some of the students who were interviewed to feel less motivated to learn in class, especially in science subjects. Retrieval of data using random sampling method. This research was conducted at SMP N 9 Dumoga with 70 respondents in grades VII and VII of junior high school who were active in the 2020/2021 school year. To determine the level of parental attention and student learning motivation, the mean score is used. Retrieval of data using the convenience sampling method. To determine the level of parental attention and student learning motivation used the mean score. Pearson correlation was used to find out whether there was a significant relationship between parental attention and students' learning motivation in science subjects. The results of this study showed that there was no significant relationship between parental attention and students' learning motivation